PTU-030 Obesity: a risk factor for Crohn's disease or a distinct obesity-related enteropathy?. (23rd September 2015) - Mendall, M; Gunasekera, A V; John, J B; Kumar, D
Abstract : Introduction: Obesity is a rapidly increasing problem with an increasing number of adverse health consequences being discovered. It is associated with a pro-inflammatory state.1 In epidemiological studies obesity has been associated with diarrhoeal symptoms, 2 and increased levels of a marker of inflammation, calprotectin, in the faeces.3 The objective was to determine whether obesity at diagnosis is a risk factor for Crohn's disease vs ulcerative colitis and also vs community controls. Methods: 524 consecutive patients attending gastroenterology clinics at Mayday University Hospital and St George's Medical School were administered a questionnaire enquiring about weight at diagnosis if not available from the notes and height as well as other risk factors for inflammatory bowel disease. 480 community controls aged 50–70 were randomly selected from the registers of 4 local general practices as part of another study. Outcome measures: odds ratio of association of obesity at diagnosis with Crohn's disease vs ulcerative colitis at all ages and Crohn's disease vs community controls in the 50–70-year age group as a secondary analysis. Results: Obesity at diagnosis was more common in subjects with Crohn's disease vs ulcerative colitis odds ratio 2.017 (1.18–3.43) p=0.01 and also Crohn's disease vs community controls in the 50–70-year age group odds ratio 3.22 (1.59–6.52) p=0.001 after controlling for age at diagnosis, sex and smoking at the time of diagnosis. The strength of association for CD vs UC was increased further after adjustment for weight and height at diagnosis to odds ratio 3.84 (1.83–8.15) p=0.0003 as was the case when BMI and BMI squared were modelled as the explanatory variables. This reflects a U shaped relationship between BMI at diagnosis and risk of Crohn's vs ulcerative colitis. Conclusion: Obesity may play a role in the pathogenesis of Crohn's disease and it maybe that an obesity related enteropathy is a distinct entity.